Nipping Temptation in the Bud: Examining Strategic Self-Control in Daily Life. (June 2020) - Williamson, Laverl Z.; Wilkowski, Benjamin M.
Self-control is often thought to be reactive and focused solely on the inhibition of responses elicited by temptations. In two studies, we assessed whether self-control can instead (a) be planned and (b) target the antecedents of the response to temptation. We assessed self-control planning, four antecedent-focused self-control strategies (i.e., situation-selection, situation-modification, distraction, and reappraisal) and one response-focused strategy (i.e., response-inhibition). In both studies, we found that self-control planning predicted the initiation of self-control independently of temptation. Each antecedent-focused self-control strategy uniquely predicted goal-progress. Response-inhibition did not produce consistent effects on goal-progress. These studies provide evidence that people proactively initiate self-control by targeting the antecedents of temptation and that doing so supports goal-progress.